Changes in the Dietary Inflammatory Index Over Time and Cancer Development Within Rural Post-Menopausal Women. (29th May 2020) - Dougherty, Mariah; Lappe, Joan; Watson, Patrice; Travers-Gustafson, Dianne; Recker, Robert; Garland, Cedric; Gorham, Edward; Baggerly, Keith; McDonnell, Sharon; Ma, Jihyun; Lyden, Elizabeth; Hanson, Corrine
Abstract: Objectives: The objective of this study was to determine the extent to which diets with a higher inflammatory potential, as measured by the Dietary Inflammatory Index (DII), are associated with cancer development in a cohort of rural post-menopausal women. Methods: This study was a secondary analysis of participants of a randomized control trial evaluating the effect of vitamin D and calcium supplementation on cancer development in rural, post-menopausal women in Nebraska. From this cohort, diets were evaluated via a 2005 Block Food Frequency Questionnaire (FFQ) at baseline and four years later (Visit 9). DII scores were calculated at both time points for each participant, including an unadjusted and energy-adjusted DII score. The relationship with DII scores and cancer development were evaluated using a chi-squared test and logistic regression, controlling for pertinent confounders. The difference in DII scores at baseline and Visit 9 for participants who developed cancer and non-cancer participants was examined via a repeated measure ANOVA test. Results: There were 1977 participants with baseline and Visit 9 DII scores available for analysis. There was a significant difference in DII scores between baseline and Visit 9, with a significantly larger change in DII scores in the participants who developed cancer (p = 0.0194), shifting to higher pro-inflammatory scores at Visit 9. Cancer status was not associated with baseline DII scores, nor was DII score a predictor of cancer status, when controlling for confounders. Conclusions: These findings illustrate how dietary patterns in persons diagnosed with cancer had significant changes over time, increasing inflammatory diet potential. This increase in inflammatory potential in cancer patients may impact outcomes like treatment success, overall survival, and cancer recurrence, creating a need for more research to further analyze the impact of cancer diagnoses on diet changes, and if these changes are detrimental to cancer survivor outcomes. Funding Sources: None.